Pedagogy: Implementation of the “Hong Ik In Ngan” Values Learning for Korean Learnes - Eo, Yoon Kyung; Nuryani, Pupun; Hikamudin, Eviana; Solahudin, M. Nizan (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
This article discusses the pedagogical meaning of implementing